Dopolnitel'noe professional'noe obrazovanie kak faktor razvitija psichologiceskogo zdorov'ja trenerskich kadrov - Dolmatova, T. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The paper describes the results of study of reflexivity as a component of psychological health and a mechanism for professional skills excellence among coaching staff in physical culture and sports. The analysis was made on the base of 60 experts' opinion received via anonymous online survey. The correlation between the level of psychological health of sports coaches and their motivation towards upgrade of the professional skills through the lifelong learning is revealed. Thus, further professional education could be considered as a tool for professional skills upgrade as well as a factor that contributes to psychological health for sports coaches is concluded in the article.